Developing Arabic Textbook Material for Junior High School Students - Shafruddin Tajuddin; Muhammad Kamal Abdul Hakim; R.A. Barnabas (Arabic Education Program IAIN Pekalongan, 2020)
This research aims to develop Arabic textbook material for the Junior High School level. It used a research and development approach that involves 10 steps. The research began with a survey to obtain empirical data related to the Arabic language learning in Junior High School. It found that (1) the competency standard concerning the application of linguistic elements that must be mastered by students was not clearly formulated; it was only a global formula included at the end of each main competencies and basic competencies determined by the Ministry of Religious Affairs in each semester in each class level. (2) The textbook authors depend much on their individual knowledge which tends to differ from one author to another. In this case, the main problem of language material is related to the lack of attention from the author in compiling textbooks systematically in accordance with the principles of gradation. This problem has helped create the impression that Arabic language is difficult to learn. (3) The textbooks developed in this study used linguistic materials that were arranged in stages with Transformational Grammar theory. This developmental study of linguistic material is a new model in developing textbooks.